Creation of a bacterial cell controlled by a chemically synthesized genome - Gibson, Daniel G; Glass, John I; Lartigue, Carole; Noskov, Vladimir N; Chuang, Ray-Yuan; Algire, Mikkel A; Benders, Gwynedd A; Montague, Michael G; Ma, Li; Moodie, Monzia M; Merryman, Chuck; Vashee, Sanjay; et al. (Science (American Association for the Advancement of Science), 2010)
We report the design, synthesis, and assembly of the 1.08-mega-base pair Mycoplasma mycoides JCVI-syn1.0 genome starting from digitized genome sequence information and its transplantation into a M. capricolum recipient cell to create new M. mycoides cells that are controlled only by the synthetic chromosome. The only DNA in the cells is the designed synthetic DNA sequence, including "watermark" sequences and other designed gene deletions and polymorphisms, and mutations acquired during the building process. The new cells have expected phenotypic properties and are capable of continuous self-replication.